2011
DOI: 10.1586/eri.11.89
|View full text |Cite
|
Sign up to set email alerts
|

Carriage ofNeisseria meningitidisin Europe: a review of studies undertaken in the region

Abstract: Meningococcal conjugate vaccines induce herd protection by preventing nasopharyngeal meningococcal acquisition, which is a prerequisite for invasive disease. Thus, meningococcal carriage epidemiology is important in understanding relationships between carriage and disease. A literature search traced information on meningococcal carriage in 27 EU countries. Meningococcal carriage prevalence differed within and between countries, varying across age groups, serogroup distribution and over time. Carriage prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 99 publications
7
60
5
1
Order By: Relevance
“…In the region of the study, vaccination coverage in infants is currently about 70%, while it is lower in teenagers (20%). This finding is consistent with the results obtained in Germinario et al (48) and with British and European data (49,50). No MenA strains were isolated.…”
Section: Discussionsupporting
confidence: 93%
“…In the region of the study, vaccination coverage in infants is currently about 70%, while it is lower in teenagers (20%). This finding is consistent with the results obtained in Germinario et al (48) and with British and European data (49,50). No MenA strains were isolated.…”
Section: Discussionsupporting
confidence: 93%
“…For a small proportion of carriers, the serogroup could not be identified which may reflect the presence of noncapsulated isolates, or those expressing capsular serogroups other than A, B, C, W or Y. These findings are consistent with a review of carriage studies undertaken in Europe, where serogroup B was found to be the dominant serogroupable meningococcus carried [3]. Further characterization by MLST indicated that a considerable proportion of the clonal complexes identified were associated with strains causing invasive disease, with 21/31 (67·7%) clonal complexes identified reflecting those isolated from confirmed cases of invasive meningococcal disease reported through routine surveillance in the European region in 2012 [23].…”
Section: Discussionsupporting
confidence: 83%
“…carriers might be highest in this age group [2,3]. The study was also restricted to a local Filipino population recruited from Manila, so caution should be exercised when extending the findings to other Southeast Asian populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 However, although the prevalence of population carriage has been studied relatively extensively in European populations, there are comparatively few carriage data available from North America. 4,5 Neisseria meningitidis is categorized into serogroups according to the structure of the capsular polysaccharide. Five serogroups-A, B, C, Y and W-135-account for almost all the disease in the USA and Canada, although at least 13 serogroups exist worldwide.…”
Section: The Changing Epidemiology Of Meningococcal Disease In North mentioning
confidence: 99%